Systematization of Nursing Care for Pregnant Women in Primary Health Care: An Integrative Literature Review - , Rebecca Máxima de Souza Lopes; , Yasmin Pacheco Ribeiro; , Fernanda Araújo Trindade; , Mônica Custódia do Couto Abreu Pamplona; , Paulo Victor Caldas Soares; , Joneson Matheus do Vale Bezerra; , Shirley Helena dos Santos Henriques da Silva; , Camila Cristina Girard Santos; , Laysa Balieiro Pinheiro; , Thaís Lopes do Amaral Uchôa; , Elem Gabriela Reis Pinheiro; , Joiley Nazaré Queiroz da Silva; et al. (Archives of Current Research International, 2025)
This study aimed to identify and analyze scientific productions that discuss the systematization of nursing care (SNC) for pregnant women within the scope of primary health care (PHC). This is an integrative literature review (ILR) carried out through searches in the Virtual Health Library (VHL), SciELO, PubMed and Google Scholar databases. Descriptors validated in DeCS/MeSH in Portuguese and English were used, such as: Systematization of Nursing Care, Pregnant Woman and Primary Health Care. The combination of Boolean operators “AND” and “OR” was used to refine data collection in the mentioned descriptors. For data analysis, "Content Analysis" was used, allowing the categorization of findings. The PRISMA Flow Diagram 2020 was used to guide the organization and selection of texts. The results were organized into five categories: 1. Impact of SNC on the quality of prenatal care; 2. Protagonism and autonomy of nurses in providing care to pregnant women; 3. Challenges in implementing SNC in PHC; 4. Contributions of SNC to promoting maternal health and preventing injuries; 5. SNC and comprehensiveness and equity of care in PHC. It is concluded that the use of SNC in PHC qualifies prenatal care, promoting nurse autonomy and better maternal and child outcomes. Its implementation contributes to the humanization and safety of care.